Change detection study for desertification using remote sensing and GIS in Chamoli district of Uttarakhand - DHARGAWE1, S.D.; BINJOLA, SONAM; GAHLOD, N.S.; PARMAR, MANISH; MEENA, R.L. (Journal of Soil and Water Conservation, 2022)
The ecosystem in arid, semi-arid and dry sub-humid region appears to undergo degradation processes generally described as desertification. The Himalayan region in India is most susceptible to the processes of desertification due to its very fragile and sensitive ecosystem. For planning and management in the area, a location specific assessment of desertification status is essential. The present study focuses on assessment of desertification status change in Chamoli district using geo-spatial approach. The study on desertification status carried out using IRS-LISS-III data on 1:50K scale for the years 2003-2005 and 2011-2013. The mapping scale on 1:50K already proved appropriate for the district level planning and management. The study confirms the maximum increase in total area of about 0.40 per cent under desertification of forest land use in the district. A significant increase in vegetation degradation of forest land use from 7.61 per cent (2003-05) to 7.99 per cent (2011-13) observed in the study area during the period. There is non-significant or slight change in vegetation degradation of scrub land category i.e. from 14.67 per cent (2003-05) to 14.70 per cent (2011-13). The results showed the highest vegetation degradation in forest class i.e. about 0.40 per cent followed by 0.03 per cent in scrub land category. The area affected by frost shattering, mass movement degradation, water erosion, Settlement and Barren/ Rocky showed no change during the study period.